50 Jahre Baumol'sche Kostenkrankheit - Jochen Hartwig; Hagen Krämer (Wirtschaftsdienst, 2017)
Vor 50 Jahren untersuchte der Ökonom William J. Baumol eine Beobachtung, die er theoretisch unterlegte: Dienstleistungen verteuern sich rascher als materielle Güter. Dieser Beitrag würdigt Baumols bahnbrechende Idee und zeigt, dass sie noch immer eine hohe theoretische und eine große praktische Relevanz aufweist. Dies betrifft zum einen die Frage, wie kulturelle, soziale und gesundheitliche Dienstleistungen finanziert werden sollen. Zum anderen leistet Baumols Idee einen Beitrag zur aktuellen Debatte über den trotz Digitalisierung geringen Produktivitätsfortschritt. – – The year 2017 marks the 50th anniversary of William J. Baumol's 'Cost Disease', which posits that services with low productivity growth become more expensive relative to goods while aggregate productivity growth slows down in the process of tertiarisation. The authors present the basic structure of Baumol's model and discuss several attempts to refute the concept or to cope with its consequences. One of them is the important observation by Nicholas Oulton that business services - unlike personal services - can contribute to higher aggregate productivity growth. A major precondition is that the productivity growth of business services is positive. However, an empirical test shows that this is not the case in Germany and other major advanced economies. Some economic policy conclusions are drawn.
Keywords: O4; O14; O47; 330